In vitro shoot regeneration from cotyledonary leaf explant of tomato variety MT1 - Kamaladini, Hossein; Abdullah, Siti Nor Akmar; Abdul Aziz, Maheran (Sarawak Biodiversity Centre, 2008)
Development of an efficient regeneration system for commercial tomato cultivars is a necessary precondition for genetic manipulation. Regeneration system of tomato variety MT1 was developed. Seeds were cultured on half strength Murashig and Skoog (MS) medium. The 12-14 days old cotyledon leaf explants were cut and cultured on full strength MS medium supplemented with 1 mg/l NAA and 1 mg/l BAP. After 48 h these explants were transferred to regeneration medium containing two types of cytokinin which were 2ip and zeatin. The concentrations used were 0, 1, 2, 3, 4, 5 mg/l for both 2ip and zeatin. High frequency of shoot regeneration by using different concentrations of 2ip was achieved on MS medium with 4 mg/l giving the best results. Meanwhile MS medium containing 2 mg/l zeatin showed highest percentage and number of shoots formed per explant. Results showed that more callus formation occurred on medium containing 2ip. Individual shoots derived from cotyledon were used for root induction. Root induction medium was MS containing 5 mg/l IAA and shoots maintained on this media for three weeks until roots were well developed. These systems would provide the means for recovering genetically modified plants after subjecting explants to Agrobacterium-mediated transformation or particle bombardment.